Meningkatkan Motivasi Belajar Siswa pada Materi Kesetaraan Laki-Laki dan Perempuan dengan Model Problem Based Learning di Kelas X Fase E SMA Negeri 2 Tarutung - Tomu jaya Tua Purba (PROSIDING SEMINAR NASIONAL PENDIDIKAN DAN AGAMA, 2024)
Learning motivation is an important factor that influences student success in learning learning process. However, students often experience a decrease in motivation to learn which can hinder the achievement of learning objectives. Therefore, there is a need for learning methods that can increase students' learning motivation. One method Effective learning in increasing students' learning motivation is the use of interesting and interactive learning media. Attractive learning media can arouse students' interest and enthusiasm in the learning process. With the existence of learning technology, students can learn independently and interactively, so that their learning motivation can increase. Apart from learning media and learning technology, management of Catholic Religious Education and Character education is also has an important role in increasing student learning motivation. Good management of Catholic Religious education will create a learning environment that is conducive, disciplined and oriented towards achieving learning goals. With good management of Catholic Religious education, students will feel comfortable and motivated to learn. In this research, it is hoped that learning methods can be found that are effective in increasing student learning motivation. It is hoped that this effective learning method can be implemented in the context of Islamic education to improve student learning achievement. By increasing student learning motivation, it is hoped that learning objectives can be achieved better.